Lipopolysaccharide-induced alterations in the liver metabolome of St. Croix and Suffolk sheep - Johnson, Samanthia R.; Bentley, Kelsey; Bowdridge, Scott; Ogunade, Ibukun M. (Frontiers in Animal Science, 2024)
The development of resistance in parasites due to overuse of anthelmintics has resulted in a marked decrease in the efficacy of these drug classes. Recent research efforts have focused on exploring alternatives such as selection for parasite-resistant breeds with the implication that immunocompetence may align with parasite resistance. Two breeds that are often investigated are the St. Croix (STC) and Suffolk (SUF). The liver plays a vital role in metabolism in the body and metabolizes LPS, which triggers response through production of metabolites and immune cells. The objective of this study was to investigate the breed differences in liver metabolome of sheep, with divergent resistance to parasites, in response to LPS. Both STC and SUF sheep (n = 9/breed) were challenged with LPS intravenously. Rectal temperatures and sheep grimace score (SGS) were recorded hourly, for each animal, and averaged across the study for both breeds. The average rectal temperature throughout the study was similar for STC and SUF sheep (40.4°C and 40.2°C respectively), but the pattern of response was different. STC had an average SGS of 0.8 while SUF had an average of 3.3. Liver biopsies were collected from 3 sheep that were not challenged with LPS (HR0; n = 3/breed), two hours post-challenge (HR2; n = 3/breed), and six hours post-challenge (HR6; n = 3/breed). Liver tissue samples were subjected to quantitative untargeted metabolome analysis using chemical isotope labelling/liquid chromatography-mass spectrometry. Pathway analysis of the HR0 metabolome data revealed that 8 pathways (and their associated metabolites) including beta-alanine metabolism, arginine and proline metabolism and glutathione metabolism were altered (false discovery rate-adjusted Pvalue (FDR) ≤ 0.05) between STC and SUF sheep. At HR2, 10 altered pathways such as folate biosynthesis, taurine and hypotaurine metabolism, and glutathione metabolism. At HR6, only 2 pathways (glycerophospholipid metabolism and purine metabolism) were altered (FDR ≤ 0.05) between STC and SUF sheep. Results highlight the differences in hepatic metabolome and physiological response to LPS challenge that exist between SUF and STC. These findings suggest breed-specific differences in metabolic response to immune challenge, potentially influencing the divergent resistance of the two breeds to parasitic infections.